PENINGKATAN SISTEM TEKNOLOGI PENGOLAHAN AIR MELALUI PENGEMBANGAN SISTEM INFORMASI - Wahyono, Heru Dwi (Jurnal Teknologi Lingkungan, 2000)
Clean water needs and wastewater treatment will be a serious problem for industry especially for food industries. The packet information of applicable technology for water treatment and industrial waste handling that can support any development sector nowadays is needed by any kind of society especially for small and medium enterprise players. To face on globalisation, the computer and information technology will be used as an important tools for distributing the packet of technology from R&D community to any kind of society through global network. By using the existing network infrastructure in the country, the packet information of technology will be distributed electronically specially to help group of small and medium industry. As pilot project, this activity chooses the tahu/tempe industry located in Semanan, Jakarta Barat for the industrial centre. By surveying the need of technology, we try to help craftsman to resolve their problem on clean water supply and industrial waste, so they can increase their product quality.